An Extended TAM Approach to Understanding Behavioral and Institutional Drivers of Drone Technology Adoption in Indonesia’s Green Economy - Khofiyah, Nida; Isna Nugraha; Hasyrani Windyatri (Journal of Advances in Information and Industrial Technology, 2025)
Indonesia’s transition toward a green economy requires the adoption of efficient and environmentally friendly technologies, including drone systems that offer substantial benefits across agriculture, forestry, and green logistics. However, adoption remains limited due to behavioral and institutional barriers. This study applies an extended Technology Acceptance Model (TAM) to examine how Environmental Concern (EC), Government Support (GS), Facilitating Conditions (FC), Perceived Ease of Use (PEOU), and Perceived Usefulness (PU) shape Behavioral Intention (BI) toward drone adoption in Indonesia. Using SEM-PLS and data from 112 practitioners and stakeholders, the results reveal that FC has a strong and significant effect on PEOU, while EC and GS do not significantly influence PU, indicating limited perceived relevance of environmental awareness and government policy in shaping usefulness perceptions. Furthermore, PEOU significantly affects PU and BI, and PU significantly enhances BI, confirming the central role of usability and functional benefits in driving adoption. These findings highlight that effective infrastructure, operational support, and usability improvements are more influential than environmental or regulatory factors in promoting drone technology. The study provides strategic recommendations for policymakers and industry actors to strengthen institutional facilitation, improve capacity building, and enhance the practical value of drones to advance Indonesia’s green economic transformation.